2013
DOI: 10.1007/s12013-013-9776-4
|View full text |Cite
|
Sign up to set email alerts
|

Cosolvents Induced Unfolding and Aggregation of Keyhole Limpet Hemocyanin

Abstract: The objective of this study was to examine the effects of 2,2,2 trifluoroethanol (TFE) and acetonitrile (ACN) on the stability, behavior, and structural characteristics of giant multimeric protein Keyhole Limpet hemocyanin (KLH) by combining the circular dichroism (CD) and fluorescence measurements of KLH solution. In concentration range 20-50% (v/v) TFE, protein at pH 7.4 shows visible aggregation while no aggregation was observed in the entire concentration range of TFE at molten globule (MG) state (pH 2.8) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Given that acetonitrile is a non-polar solvent, it can dissociate non-covalent aggregate species that are formed by hydrophobic interactions, in the same way that it minimizes the interaction between hydrophobic regions of the protein and the column resin. According to Varshney et al , 34 acetonitrile induced aggregation was observed at concentrations above 40% at pH 7.4 and above 70% at pH 2.8, confirming that high concentration of organic leads to significant loss of tertiary structure, breaking up presumed hydrophobically driven interactions and thus the formation of aggregates. We opted out using acetonitrile and moved forward with the evaluation of arginine containing mobile phase.…”
Section: Mobile Phase Screening With Acetonitrilementioning
confidence: 80%
“…Given that acetonitrile is a non-polar solvent, it can dissociate non-covalent aggregate species that are formed by hydrophobic interactions, in the same way that it minimizes the interaction between hydrophobic regions of the protein and the column resin. According to Varshney et al , 34 acetonitrile induced aggregation was observed at concentrations above 40% at pH 7.4 and above 70% at pH 2.8, confirming that high concentration of organic leads to significant loss of tertiary structure, breaking up presumed hydrophobically driven interactions and thus the formation of aggregates. We opted out using acetonitrile and moved forward with the evaluation of arginine containing mobile phase.…”
Section: Mobile Phase Screening With Acetonitrilementioning
confidence: 80%
“…A protein exists in equilibrium with unfolded conformational states in solution with the folded ensemble being favored at ambient conditions. This equilibrium between the folded and the unfolded states can be perturbed by changing the thermodynamic state of the system (temperature, pressure, and pH) or by changing the composition by the addition of co-solvents to the solution [16]. Interestingly, the effect of co-solvents on the protein can alter this equilibrium in any direction.…”
Section: Studying Folding/unfolding Transitions Of Proteinsmentioning
confidence: 99%
“…On the other hand, protective osmolytes/kosmotropes, such as trimethylamine N-oxide (TMAO), dimethyl sulphoxide (DMSO), glycine, betaine, glycerol, and sugars, induce stabilization of the folded proteins (Figure 3b). Studies on solvent-mediated structural and conformational transitions of proteins can provide insight into their stability, folding pathways, and intermolecular aggregation behavior [16,17].…”
Section: Studying Folding/unfolding Transitions Of Proteinsmentioning
confidence: 99%
“…It is also useful to understand the mode of interaction and determine the change in protein secondary structure (Rabbani and Choi, 2018;Rabbani et al, 2015). The intermolecular and intramolecular interactions involved in the protein secondary structure stability are affected upon binding with ligands or drug molecules (Varshney et al, 2014;Thakur et al, 2017). CD spectra is established with one positive spectra on 195 nm and two significant negative peaks centered on 209 nm and 222 nm in the far-UV region due to the n → π* transition that shifts the peptide bond, which is characteristic of α-helix structure (Varlan and Hillebrand, 2010;Rogozea, 2012;Suryawashi, 2016;Zhang et at., 2016).…”
Section: Measurementsmentioning
confidence: 99%